Control Strategies and Power Relations: Directive Speech Acts in Sore: Istri dari Masa Depan - Elisabeth Dwi Clara; Juni Sari Sianturi; Aulia Monica Tambunan; Partohap Saut Raja Sihombing (Yayasan Bayt Shufiya Nusantara, 2026)
Most research on directive speech acts and power relations focuses on institutional hierarchies, such as teacher–student or employer–employee interactions. However, attention to how power is constructed in the context of informational asymmetry—specifically where no legitimate social authority exists—remains relatively limited. This study fills this gap by analyzing the film Sore: Istri dari Masa Depan (2025), which presents a unique pragmatic situation where a stranger establishes dominance based solely on future knowledge. Using a descriptive qualitative design, this research integrates Searle Speech Act Theory and Fairclough Critical Discourse Analysis. The findings indicate that directive speech acts are the most dominant linguistic feature, used to regulate the interlocutor's bodily habits. The analysis demonstrates that the protagonist applies specific constraints on content to negate or override the interlocutor's agency. The study concludes that, in the absence of formal social status, authority is discursively constructed through epistemic advantage (knowledge superiority), where linguistic coercion gains legitimacy through the urgency of survival. Thus, this research contributes to the pragmatic understanding of power dynamics in high-stakes, non-institutional conflicts.